IMPLEMENTATION OF EXPERIENTIAL LEARNING APPROACH TO THE TRAINING OF CHARACTER DEVELOPMENT OF CIVIL SERVANTS IN MINISTRY OF TRANSPORTATION ENVIRONMENT - R. Berkah Anugrahwanto; Sri Nurhayati (IKIP Siliwangi Bandung, 2020)
This research aims to describe the implementation of the method of the Experiential Learning approach in character building training of Civil Servants (PNS) Ministry of Transportation at the Education Hall and character development training of human resources transportation (BP3KSDMT) Bandung. This study uses a simple research design approach with a descriptive method. The subject of this study is the rescue, teaching personnel, and trainees. Data collection is obtained through observation methods, interviews, and documentation. Techniques used to analyze data using triangulation. The data presented using descriptive techniques. The results showed that the implementation of Experiential Learning was relevant to Simon Priest's theory. The training of civil servant character development in BP3KSDMT implemented the four phases of Experiential Learning, namely Action, Reflection, Integration, and Continuation. From the side of the Maintenance Institute Training Board for the character development of the Bandung transportation HR, following Public training management is by implementing three phases, namely preparation, implementation, and evaluation training